Unsightly eyelids. - Mohd Tohit, Eusni Rahayu; Chong, Pei Pei; Abdullah, Syahrilnizam
This is a PBL case for medical students evolve around a patient with 'unsightly eye lids' who has familial hypercholestrolaemia. Students are required to discuss around the case and give outline of management.